Understanding Religion in the Era of Smart Society from the Perspective of Joachim Wach - Wiza Atholla Andriansyah; Achmad Tohari (CV. Rayyan Dwi Bharata, 2023)
Issues in the realm of religion have always been a topic of discussion that has its own charm. This study aims to explain religious experience in the 5.0 era. but with the perspective of Joachim Wach This research is a library research with a descriptive philosophical analysis method, while the theory used is the theory of religious experience according to Joachim Wach. The data collection technique used was documentation literature study. From this research we identify that religious experience can be expressed in the form of action, besides that religious expressions that appear are not only related to ritual matters, but also related to social realities such as being able to be tolerant, not exclusive and have a soul. good social. This research begins by looking at the current religious phenomenon which is the starting point of this research. The results of this study are that religious experience influences human behavior in the era of Smart Society 5.0, collaborating religious values and technological advances can produce progress for mankind.